(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
يعالج هذا البحث فعل الجسد، الذي يواجه قوى الزمان القاهرة، عبر سلوك حركي معبَّر عن انفعالات النفّس وتطلّعاتها، وبوصف الشنفرى واحداً من الصعاليك الذين واجهوا العدم المحيط بفعل جسدي مقابل، نرى أن سلوكه الفعلي كان تعويضاً عن الفقد والقهر؛ فكانت حياته حياة تأهب نفسي، واستعداد جسدي لمعركة البقاء، وكانت إرادته هي الحافز الأكبر لتحدِّي السَّلب تفوّقاً على عوامل الحرمان. وكان فعله الجسدي قويّاً، صلباً، مصوَّراً في لوحات الفتوة، يحكي سلوكه لغة المواجهة، ترشده خطط متّبعة باتجاه هدف واحد، تدفعه غريزة البقاء. فقد سعى الشنفرى إلى إيجاد ذاته الضّائعة في معمعة العدم، سعياً إلى الإحساس بالوجود، من خلال المتعة والقوة، ومن هنا كان الجسد رسالة النفس إلى الوجود. إضافة إلى ما سبق، كانت اليقظة فعل الجسد المتحفز، وكانت الإرادة تحثّ الجسد على الاستيقاظ حضوراً، والتنبّه حذراً، وخروجاً من السّبات والتشيّؤ، وتوجيه حسّ الاغتراب إلى شعوره بالانتماء. وفي لغة الصبّر كان فعل الجسد ساكناً، فالضغط الشديد على فاعليّة الحسّ فجّرَ الإرادة في تمرّدها على المألوف، فكان أن تحمّل الجسد المعاناة، والقهر، واللاّنتماء. وفي المنعة الجسدية والصلابة كان الفعل القوي، حين استمدّ الجسد منعته من مظاهر الثبات والدّيمومة، في طبيعة شبه الجزيرة العربية، تلك المظاهر التي أشبعت حاجة الشاعر إلى الإحساس بالقوة مواجهةً وتحدياً؛ فكانت الصحراء، والمرقبة، ووعل الجبال، والسلاح المعادل الموضوعي والنفسي له، وذلك حين عبّرت عمّا يجيش في نفس الشاعر من صلابة، ومنعة قاوم بهما قوى الغدر. وثار الجسد منتفضاً في فعل حركي؛ لتغيير رؤى الواقع، حين ثار جسد الشنفرى على واقعه، رداً على ضعفه، وتعويضاً عن نقصه؛ إذ عملت إرادة النفس القوية لدرء الإحساس بالضعف، حين اقتضت التغيير، وإبدال الجديد بالبائد، فكانت لغة الجسد ترجمة لجيشان النفس الثائرة، عبر فعل حركي لا يتوقف. This research deals with the acting of the body which encounters the oppressive forces of time through a motional attitude expressing the soul’s reactions and aspirations. In Ash- Shafara being one of the outlaws who confronted the surrounding deprivation in a mere physical action we could see that his active attitude was a compensation for the poverty and oppression. His life was one of psychic readiness and a physical readiness in the war of survival and his will was a very impulse to defy robbery and beat depravity factors. His physical action was strong and tough in his configurations of racketeers in his painting and his attitude speaks the language of confrontation guided by plans following one target and direction motivated by the instinct of survival. Ash –Shanfara was seeking to find lost self in the heart of nihility seeking for sense of existence through power and sexual pleasure. Hence the body was the message of the soul to the existence. In addition to the above awakening was the action of a ready body and the will was exhorting the body to rise up, he warned alarmed and redirect alienated self into a sense of belonging. And in the language of patience the body was still so extreme stress has blown up the will to rebel against the conventional so the body had to bear the suffering oppression and indifference. The body drew its physical pleasure and toughness from the aspects of firmness and perpetuity from nature in Arab peninsula. These aspects which satisfied the poet’s need to defy and confront so the desert the rank, the mountain goat and the arms were for him an objective correlative expressing his inner self toughness and redine to resist. The body revolted in a motional action to change the spectacles of the reality, Ash-Shanfara’s revolted against the reality in answer to its weakness and in compensation to its shortage. The strong will of the soul has operated to shun away the sense of weakness when it required the change and replacement of the ancient by the modern. The language of the body was an interpretation of the turbulence of the soul in rebelling through a non-stop action of motion.